How the Integrated Fishing Port with Information System for Sustainability (INFINITY) realizes governance of Green Fishing Port - Ni Putu Eka Widiastuti; Kusumajanti Kusumajanti; Asep Kamaluddin Nashir (Cogent Business & Management, 2024)
This paper aims to achieve environmental and economic sustainability in maritime affairs through Green Fishing Ports (GFP). The governance of Fishing Ports with an integrated information system in Indonesia (as a maritime nation) is an intriguing issue for realizing sustainable underwater development, enhancing operational efficiency, improving safety and comfort, and boosting the economic well-being of coastal communities. An effort to achieve that is the management of integrated digital Fishing Ports. This paper employs qualitative research with a comparative case study of the Nizam Zachman Ocean Fishing Port in DKI Jakarta and the Karangantu Archipelago Fishing Port in Banten Province. Data collection utilizes unstructured interviews with six informants knowledgeable in port governance. This paper reveals that the governance of the Nizam Zachman and Karangantu Fishing Ports have operations with an `Integrated Fishing Port with Information System for Sustainability' concept—abbreviated as INFINITY. Through the implementation of INFINITY, the governance of fishing ports can be significantly enhanced. The utilization of INFINITY has led to notable improvements such as increased fish production values, enhanced cooperation within the fisheries sector, and the promotion of marine resource sustainability, thereby contributing to the advancement of a green economy.
Keywords: 650; Environmental and economic sustainability; governance of Green Fishing Port; integrated fishing port with information system for sustainability; infinity; Green economy